Horizontal gene transfer from genetically modified plants - Regulatory considerations - Philips, Joshua G.; Martin-Avila, Elena; Robold, Andrea V. (Frontiers in Bioengineering and Biotechnology, 2022)
Gene technology regulators receive applications seeking permission for the environmental release of genetically modified (GM) plants, many of which possess beneficial traits such as improved production, enhanced nutrition and resistance to drought, pests and diseases. The regulators must assess the risks to human and animal health and to the environment from releasing these GM plants. One such consideration, of many, is the likelihood and potential consequence of the introduced or modified DNA being transferred to other organisms, including people. While such gene transfer is most likely to occur to sexually compatible relatives (vertical gene transfer), horizontal gene transfer (HGT), which is the acquisition of genetic material that has not been inherited from a parent, is also a possibility considered during these assessments. Advances in HGT detection, aided by next generation sequencing, have demonstrated that HGT occurrence may have been previously underestimated. In this review, we provide updated evidence on the likelihood, factors and the barriers for the introduced or modified DNA in GM plants to be horizontally transferred into a variety of recipients. We present the legislation and frameworks the Australian Gene Technology Regulator adheres to with respect to the consideration of risks posed by HGT. Such a perspective may generally be applicable to regulators in other jurisdictions as well as to commercial and research organisations who develop GM plants.